Analyzing the Strelitzia Juncea Cellulosic Fibers Mechanical Properties Experimental Data Using Various Statistical Methods - Teyar, Soumia; Gheribi, Hassina; Boumaaza, Messaouda; Belaadi, Ahmed; Chai, Boon Xian; Abdullah, Mahmood M. S.; Alshaikh, Ibrahim M. H.; Al-Khawlani, Amar; Ghernaout, Djamel (Taylor & Francis, 2024)
Manufacturing composites using natural fibers support the development of more ecologically friendly applications in many industrial areas, including sports equipment, wind turbine blades, construction materials, packaging, medical devices, and prosthetics. To investigate the tests number (N) impact on the fibers tensile behavior, newly developed fibers from the Strelitzia juncea (SJ) plant are being studied for their mechanical properties using various statistical laws. This study aims to assess the SJ fibers performance with a gauge length of 50?mm under quasi-static stress conditions. 150 SJ fibers were tensile tested in five groups (30, 60, 90, 120, and 150) to determine the N impact on the fibers tensile strength, break deformation, and Youngs modulus. Weibull and log-normal distributions were used to study statistically the mechanical properties results, and their dispersion was investigated and quantified using least squares and maximum likelihood prediction model with a confidence level of 95%.